Emergency Food Product Packaging by Pectin-Based Antimicrobial Coatings Functionalized by Pomegranate Peel Extracts - Ehsan Ghorbani; Arasb Dabbagh Moghaddam; Anousheh Sharifan; Hossein Kiani (Journal of Food Quality)
Emergency food products (EFPs) or energy bars are used in critical situations, such as natural disasters, to promote crisis management. EFPs require sophisticated packaging strategies. Edible coatings incorporated with natural antimicrobial agents could be considered as active packaging materials for increasing EFP safety. In this study, pectin-based coatings incorporated with pomegranate peel extracts were used to protect energy bars. Initially, total phenolic contents and antimicrobial and antioxidant properties of aqueous and ethanolic pomegranate peel extracts (PPEs) were determined. Also, PPEs were analyzed by HPLC. In the next step, the extracts were incorporated into the matrix of edible coatings as active substances. The sensory properties and microbial contamination of coated energy bars were investigated during 30 days of storage. Sixteen phenolic substances were detected in the extracts with gallic acid, ellagic acid, caffeic acid, coumaric acid, and quercetin as major ingredients. The ethanolic extract exhibited higher concentrations for all phenolic compounds. The results indicated that the ethanolic extract showed inhibitory effects on S. aureus and E. coli at concentrations of 30 and 50 mg/ml, and the aqueous extract's inhibitory effects were observed at concentrations of 50 and 80 mg/ml, respectively. The antioxidant and antibacterial effects could be attributed to high phenolic content and a combination of different substances. Microbial and sensory tests performed on coated energy bars showed that the active coatings were able to control and reduce the population of microorganisms during storage without adversely affecting sensory properties.